Preliminary report on social acceptance and behaviours towards water-smart solutions (Deliverable 5.4, B-WaterSmart project) - Gomes, Carla (2023)
This report of Work Package 5 – Society, Governance, Policy corresponds to “D5.4 - Preliminary report on social acceptance and behaviours towards water-smart solutions (M36). It is one of the outputs from Task 5.3 - Assessment of stakeholders’ attitudes towards water-smart solutions, which aims to analyse perceptions, practices, and attitudes throughout the Project. It aims at a preliminary analysis of results from the CoP meetings and stakeholder interviews regarding issues of acceptance of water-smart solutions by policymakers, stakeholders, end-users, and the public. The report applied the social acceptance analytical model, developed in the project’s Milestone 7 document (July 2021). Among other key concepts, it considers risk perceptions, justice and fairness notions, and trust between stakeholders, in authorities and companies. D5.4 is a preliminary report, of which there will be a final version in M48 of the project.